Pengaruh Viral Marketing, Celebrity Endorser, dan Brand Awareness Terhadap Keputusan Pembelian Skintific - Eunike Freskanta Bukit; Femmy Femmy; Francisca Dewanti Mayangsari (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
The widespread development of the internet has encouraged many cosmetic brands to adopt marketing strategies that focus on utilizing online platforms. They use the internet as a means to communicate, convey information, and promote their brand to consumers. This study aims to examine the effect of viral marketing, celebrity endorsers, and brand awareness on purchasing decisions for the Skintific cosmetic brand. The sampling method used was non-probability sampling with 112 respondents. Data collection was carried out through questionnaires, and the data analysis technique used was multiple linear regression test. The results showed that viral marketing, celebrity endorsers, and brand awareness together have a significant influence on purchasing decisions for the Skintific cosmetic brand. In addition, partially, viral marketing variables, celebrity endorsers and brand awareness also have a significant influence on purchasing decisions.